PENGARUH CORPORATE SOCIAL RESPONSIBILTY TERHADAP LOYALITAS KONSUMEN MELALUI EVALUASI PERUSAHAAN (Fokus Ekonomi, 2010)
The demand of doing CSR is increasing nowadays include corporate in Indonesia, especially when they will go global or only cooperate with corporate from developed countries. Consumer often chooses corporate that makes feel being have social responsibility when they buy the product, thus CSR is one of domain criteria in consumer’s purchase decision making. This research uses the technique of purposive sampling. Technique of data processing use SPSS 11.5 while data technique analyzing used in this research is simple linear regression analysis. Pursuant to hypothesis test t which have been conducted to be obtained by P value that is 0.387 and 0.384, where P value > from a that is 0.05. Pursuant to the P value result, inferential hence Ho accepted and H1 and H2 refused, what it’s meaning that CSR not influence company evaluation and company evaluation also not influence to consumer loyalty.